SEASONAL STRESS ON FATTY ACIDS IN COMMON CARP WITH RELATION TO ACETYL CHOLINE ESTERASE - S.MD.M.N. IQBAL; P. INDIRA (International Journal of Pharma and Bio Sciences, 2014)
Summer season with 300C is taken as control, where as rainy season with 200C is taken as cold stress and winter season with 150C is taken as cold adaptation. During summer season (control) The Acetyl Choline Esterase Increases, fats decreases and fatty acids increases. The fatty acids are utilized by the fish for its strenuous activity during summer. During Rainy, season due to cold stress the fats increases and fatty acids decreases. In winter season due to cold adaptation the fats decreases and fatty acids increases with regard to tissue variation during cold stress the fats is more and fatty acids are less in osmotic tissues and facts are less and fatty acids are more in non osmotic tissues. Less AchE is synthesized in non osmotic tissues and more in osmotic tissues. In case of species variations during cold stress AchE is more in cyprinus carpio followed by labeo rohita and least in Catla Catla whereas, fats occurs invise versa.